Diagnóstico geoambiental com uso do geoprocessamento visando a determinação de potencialidades de uso do solo para a área estuarina do Rio Curimataú - Canguaretama(RN) - Fernandes, Rodrigo Cysneiros (2006)
The activities developed in the coastal zone always arise the researchers interest, mainly when it is developed in fragile ecological areas, not observing the sustenable development laws. In this context, the analysis presented developed around the estuary of Curimatau river, located in the Eastern coast of Rio Grande do Norte state, integrates information provided by high resolution images of orbital remote sensing (IKONOS II, dated of July of 2003) and images of not-orbital remote sensing (Air photographs of DPU, dated of March of 1997) in a multitemporary perspective, diagnosising patterns of use and occupation, evaluating the main area´s impacts, together with the estuarian region fisiograph of Curimatau river. The use of high resolution images consequently allowed generates a precision cartography, facilitating the quantification of the evolution of the landscape and supporting decisions. Was possible yet, the definition of use areas, conservation areas and preservation areas; that were inserted in the concept of Potentialities: a fundamental element to management of vulnerable areas of the natural point of view. The information provided during the research had been stored in an Enviromental Georreferenced Data Base, constructed under the optics of Geographical Information Systems (GIS), that they facilitate the environment management Through fast access to information. The results were satisfactory, because permits the quantification of evolution of the landscape and the mapping. Beyond the geoenviromental diagnosis, was possible develop maps and matrixes that support the Rio Grande do Norte state costal Management.